Sexual and Reproductive Justice: From the Margins to the Centre - Morison, Tracy; Mavuso, Jabulile Mary-Jane Jace (Lexington Books, 2022)
Sexual and Reproductive Justice: From the Margins to the Centre offers new insights and perspectives on sexual and reproductive justice. The thought-provoking and diverse contributions in this volume — which range from indigenous approaches to sexual violence to gender-affirming primary and mental healthcare — extend sexual and reproductive justice scholarship, and spark critical questions, novel thinking, and ongoing dialogue in this field.